Determinant auditor switching pada perusahaan terdampak Covid-19 yang terdaftar di Bursa Efek Indonesia tahun 2017-2021 - Adityaningrum, Utami; Yendrawati, Reni (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
This study aims to determine the effect of audit opinion, financial distress, management change and firm size on auditor switching. This study uses a quantitative model with data collection methods using purposive sampling of companies effected by Covid-19 there for: health company, insurance company, logistics company telecomunication cmpany listed on the BEI for period 2017-2021. There are 46 companies and 230 samples. The results of this study indicate that: 1) It is proven that opinion audit has a positive effect on auditor switching 2) financial distress has a positive effect on auditor switching 3) company size has been proven to have a negative effect on auditor switching; 4) management change has no effect on auditor switching.